2001
DOI: 10.1007/s001920170087
|View full text |Cite
|
Sign up to set email alerts
|

The Pain Cycle: Implications for the Diagnosis and Treatment of Pelvic Pain Syndromes

Abstract: The aim of the study was to report our results of sacral nerve stimulation in patients with pelvic pain after failed conservative treatment. From 1992 to August 1998 we treated 111 patients (40 males, 71 females, ages 46 +/- 16 years) with chronic pelvic pain. All patients with causal treatment were excluded from this study. Pelvic floor training, transcutaneous electrical nerve stimulation (TENS) and intrarectal or intravaginal electrostimulation were applied and sacral nerve stimulation was used for therapy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 7 publications
2
58
0
Order By: Relevance
“…Everaert et al 55 also treated a series of chronic pelvic pain and reported that success was inversely related to neuropathic pain, but that the 11 patients who responded appeared to have a durable response to ϳ3 years. A subsequent series of 21 implanted patients with interstitial cystitis, reported by Peters and Konstandt, 56 were followed for a mean of 15 months.…”
Section: Figmentioning
confidence: 99%
“…Everaert et al 55 also treated a series of chronic pelvic pain and reported that success was inversely related to neuropathic pain, but that the 11 patients who responded appeared to have a durable response to ϳ3 years. A subsequent series of 21 implanted patients with interstitial cystitis, reported by Peters and Konstandt, 56 were followed for a mean of 15 months.…”
Section: Figmentioning
confidence: 99%
“…10 Promising results are being reported in conditions, such as pelvic pain syndrome and interstitial cystitis. [11][12][13][14][15] Few papers reported the effect of SNM therapy on female sexual function in mixed population groups with voiding dysfunction, fecal incontinence, 16 and chronic pelvic pain. [17][18] It is uncertain if the reported effect of SNM therapy in female sexual function is direct to stimulation or secondary to primary disease therapy and overall improved quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Everaert et al [23], treating a series of chronic pelvic pain, reported that success was inversely related to neuropathic pain, but that the 11 patients who responded appeared to have a lasting response up to 3 years. In both case seriers a continuous SNM was used for therapy resistant pain.…”
Section: Discussionmentioning
confidence: 99%
“…Though the exact pathogenesis of CPPS remains unknown, in these patients pelvic floor hyperactivity and pelvic congestion are a common phenomenon [23,25].…”
Section: Discussionmentioning
confidence: 99%